PENDEKATAN SOSIOLOGI DAN ANTROPOLOGI SEBAGAI SOLUSI ALTERNATIF MODERASI BERAGAMA DI INDONESIA - Moh Asvin Abdurrohman; Moh Hazim Ahrori; Ratna Pangastuti (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This article discusses the role of sociological and anthropological approaches in solving the problem of religious moderation as a study of Islamic studies in Indonesia. The author explains how social, cultural, and religious factors influence religious views and practices in Indonesia and how sociological and anthropological approaches can help us understand and manage differences in religion and achieve harmony among religious communities. The sociological approach to the study of religious moderation can help us understand how social and cultural factors influence people's views of religion. In addition, this approach can also help us understand how religion is practiced in society and how social, economic, and political factors influence religious practice. An anthropological approach can help us understand how cultural values and traditions influence religious views and practices. By understanding the social, cultural, and religious factors that influence religious moderation, we can develop appropriate approaches and strategies to increase tolerance and harmony among religious communities in Indonesia. Therefore, sociological and anthropological approaches can make an important contribution to solving the problem of religious moderation in Indonesia.